Meningkatkan Kemampuan Bahasa Inggris melalui English Club dalam Pengabdian Masyarakat MBKM Asistensi Mengajar - Windy Annastasia Maharani; Hesty Widiastuty (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The community service program carried out by MBKM (Merdeka Belajar Kampus Merdeka) Teaching Assistance in English Education Students IAIN Palangka Raya is titled “English Club.” It aims to improve the English skills of participants at the Secondary Level. This program introduces interactive learning methods and enjoyable media through a game-based approach and technology. Thus, this activity helps participants understand English material more easily and effectively. The program is conducted over three sessions, covering topics such as self-introduction, telling time, and hobbies. Each session is designed to develop the participants' English language abilities by optimally combining theory and practice. To create an active and engaging learning environment, the activities also include educational games, such as “Hi! My Name Is...,” “Catch It!,” and “Simon Says!”, which are designed to sharpen the cognitive and motor skills of the participants. In each session, technology media, such as engaging PowerPoint presentations and online games, are used to create variety in the learning experience, making participants feel interested and motivated. The results of this activity indicate an improvement in the participants' English skills, particularly in speaking. Additionally, there is also an increase in the participants' interest and motivation toward learning English. The use of creative methods and technology has proven effective in helping participants understand the material and creating a positive learning atmosphere. In conclusion, enjoyable learning not only enhances the English skills of participants but also builds their confidence in communication.